Type-2 Neutrosophic Sets (T2NSs) for Quality Evaluation of Project-Based Art and Design Courses: Evaluation Seven Projects - Ruijuan Zhang (Neutrosophic Sets and Systems)
Conflicting objectives for alternatives must be valued in a decision-making process, and the optimal option must be chosen based on the decision-makers requirements. For this selection, multi-objective optimization techniques might offer a solution. The purpose of this study is to introduce two relatively new multi-objective optimization techniques: multi-objective optimization based on simple ratio analysis (MOOSRA) and Entropy methods. This study uses the multi-criteria decision-making method (MCDM) to evaluate the project-based art and design courses. The entropy method is used to compute the criteria weights and the MOOSRA method is used to rank the alternatives. The MCDM method is used under the type-2 neutrosophic sets (T2NSs) to deal with vague and uncertain information. A case study with 14 criteria and seven projects are used in this study. The results show that Graphic Design Projects have the highest rank and the Product & Industrial Design has the lowest rank. Sensitivity analysis was conducted to show the different ranks of alternatives.